1999
DOI: 10.1021/np990109o
|View full text |Cite
|
Sign up to set email alerts
|

A New Diels−Alder-Type Adduct Flavonoid from Dorstenia barteri

Abstract: A new Diels-Alder-type adduct, dorstenone (1), was isolated from Dorstenia barteri together with three known flavonoids, 4,2', 4'-trihydoxy-3'-prenylchalcone; 4,2',4'-trihydoxy-3, 3'-diprenylchalcone; and 5,7,4'-trihydoxy-8-prenylflavone. The structure of 1 was elucidated using a combination of highfield NMR techniques, particularly, gradient-enhanced HMQC and HMBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Phytochemical screening of the extracts showed the occurrence of flavonoids, terpenes and sterols. Flavonoids and polyphenolic compounds have been reported from many Dorstenia species (Tsopmo et al, 1998(Tsopmo et al, ,1999Dufall et al, 2003;Kansci et al, 2003;Abegaz et al, 2004;Ngameni et al, 2004). They occur as monoprenylated, diprenylated and geranylated derivatives including chalcones and other flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical screening of the extracts showed the occurrence of flavonoids, terpenes and sterols. Flavonoids and polyphenolic compounds have been reported from many Dorstenia species (Tsopmo et al, 1998(Tsopmo et al, ,1999Dufall et al, 2003;Kansci et al, 2003;Abegaz et al, 2004;Ngameni et al, 2004). They occur as monoprenylated, diprenylated and geranylated derivatives including chalcones and other flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…These were subjected to further purification by MPLC. Eventually, 150 mg of 1 were isolated after additional purification by Sephadex LH‐20 GPC 19. Similarly, Boyom and co‐workers isolated 15 mg from 450 g of powdered twigs,20 and Akihisa et al isolated 30 mg from 300 g of dried plant material 16.…”
Section: Introductionmentioning
confidence: 99%
“…23 To the best of our knowledge, no pharmacological studies have yet been made on this plant. While a previous phytochemical investigation of the same taxon afforded: 5,7,4'-trihydroxy-8-prenylflavone, isobavachalcone (1), stipulin (5) and bichalcone, 12 only isobavachalcone (1) and stipulin (5) were isolated again from this species in our study, and this variation observed in the chemical constitution may potentially be accounted for by the climatic condition, the period and area of plant collection.…”
Section: Introductionmentioning
confidence: 41%
“…Flavonoids, particularly 4-hydroxylonchocarpin (2) isolated from D. mannii, 10 are good chemopreventive molecules against ovarian cancer cell growth. Recently, isobavachalcone (1) and dorsmannin A (6) isolated from D. barteri Bureau 12 and D. mannii, 10 exhibited inhibitory effects on skin tumor promotion in an in vivo two-stage mouse skin carcinogenesis test. 13 As part of a screening program on active ingredients isolated from Dorstenia species and other natural products having antitumor properties, the aim of the present investigation is to explore the potential inhibitory effect of chalcones isolated from the twigs of D. barteri var.…”
Section: Introductionmentioning
confidence: 99%